Decision Support System for Selecting the Best Internship Students using SAW Method - Siringo-Ringo, Eko Deswin; Sugara, Heru (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The goal of this study is to find a solution to the issue of choosing the best student internship for the BPKD office in Pematangsiantar city. This office chooses the best interns candidates in order to hire candidates who are competent, skilled, able to improve their adaptability and perception in improving their performance and carrying out the tasks assigned. A Decision Support System (DSS) powered by computers is used to carry out this selection. The SAW approach is applied by the decision support system. Responsibility, Delay, Attitudes/Ethics, Presence, and Cooperation are the criteria employed in this strategy. The results of the study include recommendations for the top interns, with Mona Rachel Sitohang coming in at number one with an alternative value of 0.7500, followed by Irviana Soneta Manalu at number two with a value of 0.7042, and Elsa Paulina Simanjuntak at number three with a value of 0.6042. This office may find it simpler to choose the top students internship candidates with the use of this decision assistance system.